(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
The increasing concern about environmental and health topics generates negative public reaction when the construction of an industrial facility that emits pollutants into the atmosphere is announced. This paper proposes a methodology for industrial facility location. This methodology considers preselection, assessment and establishment of potential sites. In addition, it seeks to ensure compliance with legislation regarding pollution receipt though including parameters previously obtained by spatial diffusion models of contaminants into multiobjective facility location model. An application case from a group of brickwork industries in Yahualica, Jalisco, Mexico is solved. The results show that alternative configurations obtained contribute to economic feasibility, social justice and compliance of pollution parameters which are legally established.